Comparative Immunomodulatory Evaluation of the Receptor Binding Domain of the SARS-CoV-2 Spike Protein; a Potential Vaccine Candidate Which Imparts Potent Humoral and Th1 Type Immune Response in a Mouse Model - Shrivastava, Tripti; Singh, Balwant; Rizvi, Zaigham Abbas; Verma, Rohit; Goswami, Sandeep; Vishwakarma, Preeti; Jakhar, Kamini; Sonar, Sudipta; Mani, Shailendra; Bhattacharyya, Sankar; Awasthi, Amit; Surjit, Milan (Frontiers in Immunology, 2021)
The newly emerged novel coronavirus, SARS CoV-2, the causative agent of COVID-19 has proven to be a threat to the human race globally, thus, vaccine development against SARS CoV-2 is an unmet need to drive the mass vaccination efforts. The Receptor binding domain of the spike protein of coronavirus has multiple neutralizing epitopes and is associated with viral entry. Here we have designed and characterized the SARS CoV-2 spike protein fragment (330-526) as Receptor Binding Domain (RBD330-526) with two native glycosylation sites (N331 and N343); as a potential subunit vaccine candidate. We initially characterized the RBD330-526 biochemically and investigated its thermal stability, humoral and T cell immune response of various RBD protein formulations (with or without adjuvant) to evaluate the inherent immunogenicity and immunomodulatory effect. Our result showed that the purified RBD immunogen is stable up to 72 hours, without any apparent loss in affinity or specificity of interaction with the ACE2 receptor. Upon immunization in mice, RBD generates high titer humoral response, elevated IFN-γ producing CD4+ cells, cytotoxic T cells and robust neutralizing antibodies against live SARS CoV-2 virus. Our results collectively support the potential of RBD330-526 as a promising vaccine candidate against the SARS CoV-2.